Induction of Diploid Androgenesis in the Stinging Catfish, Heteropneustes fossilis. Issue 5 (October 2014) - Christopher, J. G.; Murugesan, A. G.; Sukumaran, N.
Abstract This study reports the results on induced diploid androgenesis in the Indian catfish, Heteropneustes fossilis. Ultraviolet (UV) irradiation was used to inactivate maternal genome of H. fossilis. Complete inactivation of maternal genome was recorded at 12, 500 ergs/mm2. These genome‐inactivated eggs of H. fossilis were inseminated with conspecific sperm. The sperm suspension was diluted to 1 × 107 sperm ml/L in Hank's Balanced Salt Solution. Egg viability was assessed for different exposure durations at fertilization, hatching, haploidy, and diploidization. Majority of the larvae derived from irradiated eggs had abnormal appearance. Complete inactivation of maternal genome was detected by haploid syndrome and confirmed by chromosome counting (n = 29). These eggs activated with sperm were subjected to heat shock at 40 and 41 C for different postactivation times and durations. Diploid androgens had a normal appearance as controls and confirmed by chromosome counting (n = 58). A maximum of 21 and 14% of diploidization was recorded at 30 min after activation, at 40 and 41 C, which corresponds to the first cleavage suppression time.